2011
DOI: 10.1017/s1755773911000117
|View full text |Cite
|
Sign up to set email alerts
|

Why a right-wing populist party emerged in France but not in Germany: cleavages and actors in the formation of a new cultural divide

Abstract: This article analyzes why, despite similar transformations in the dimensions structuring political space since the late 1980s, extreme right-wing populist parties have emerged in some West European countries, but not in others. Two factors may affect the fortunes of these parties. First, if electorates remain firmly entrenched in older cleavages, new parties will find it difficult to establish themselves. Second, the positions of the established actors with respect to the new cultural divide that the extreme p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 43 publications
3
21
0
Order By: Relevance
“…At the same time, these electorates display some overlap with those supporting the SVP, although this is less pronounced in 2011 than in earlier elections. These results lend support to arguments emphasizing issue ownership, which suggest that it is difficult for the established parties to compete with and crowd out the populist right once these parties are firmly institutionalized (Ellinas ; Kitschelt ; Bornschier ).…”
Section: The Emergence Of a Polarized New Cultural Dividesupporting
confidence: 69%
See 2 more Smart Citations
“…At the same time, these electorates display some overlap with those supporting the SVP, although this is less pronounced in 2011 than in earlier elections. These results lend support to arguments emphasizing issue ownership, which suggest that it is difficult for the established parties to compete with and crowd out the populist right once these parties are firmly institutionalized (Ellinas ; Kitschelt ; Bornschier ).…”
Section: The Emergence Of a Polarized New Cultural Dividesupporting
confidence: 69%
“…A number of new parties of the left emerged in the late 1970s and early 1980s, the Progressive Organizations (POCH), the Trotskyists, and the Greens. As elsewhere in Western Europe, but more decidedly than in other countries, the Swiss Social Democrats took up the issues of the New Left (Rennwald and Evans ; Bornschier ). Even as the smaller progressive parties receded and their voters absorbed by the Greens and the Social Democrats (Ladner ), the Swiss party system thus remained characterized by an exceptionally strong universalistic pole along the new cultural divide.…”
Section: The Transformation Of Cultural Conflicts and The Dimensionalmentioning
confidence: 99%
See 1 more Smart Citation
“…This position was consistent with the polarising strategy pursued by the Left in France since the early 1980s, whereby the PS in particular had progressively moved towards the libertarian pole of the cultural axis (Bornschier, 2012), reflecting in part the structural change in its electoral support and the development of a more urban, younger, educated middle-class clientele -the so-called bourgeois bohèmes.…”
Section: The Left's Agenda Of Cultural Liberalisationsupporting
confidence: 70%
“…Previous research on the electoral fortune of PRR parties in Western Europe (e.g. Ignazi 2003;Meguid 2008;Ellinas 2010;Bornschier 2012) has shown that if mainstream parties are able to include to some extent in their agendas whatever issues these new parties are trying to politicise, the mobilisation space for political newcomers is limited. Thus, patterns of party competition are relevant to understanding the electoral fate of the PRR.…”
Section: Supply-side Factorsmentioning
confidence: 99%